The Effectiveness of the Program Keluarga Harapan (PKH) in Reducing Poverty in Molibagu Village, South Bolaang Mongondow Regency - Claudea Anisa Adam; Frahmawati Bumulo; Fatmawaty Damiti; Melizubaida Mahmud; Rierind Koniyo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to find out how Program Keluarga Harapan (PKH) in reducing poverty in Molibagu Village, Bolaang Uki District, South Bolaang Mongondow Regency and analyze what factors affect the effectiveness of Program Keluarga Harapan (PKH) in reducing poverty in Molibagu Village, Bolaang Uki District, South Bolaang Mongondow Regency. By using a qualitative method, a descriptive approach with an ethnographic research design. Data collection techniques through interviews, observations and documentation. Data analysis is carried out by means of data reduction, data presentation, and conclusion drawn. The results of the study show that Program Keluarga Harapan (PKH) in Molibagu Village, Bolaang Uki District, South Bolaang Mongondow Regency aims to reduce poverty by providing cash assistance to very poor families, especially those who have vulnerable members such as toddlers, pregnant women, school-age children, the elderly, and people with disabilities. Through this assistance, Program Keluarga Harapan (PKH) focuses on increasing family access to education, health, and welfare, so that it can reduce the economic burden they face. The factors that affect the effectiveness of Program Keluarga Harapan (PKH) in Molibagu Village, Bolaang Uki District are internal and external factors. Internal factors ensure the effectiveness of Program Keluarga Harapan (PKH) by ensuring the accuracy of aid receipts, smooth administration, recipient satisfaction, and officer performance in data collection, distribution, and mentoring. External factors focus on improving family welfare through access to quality education, as well as the social and economic impacts that can be obtained from employment opportunities, business capital, and market support that support family economic development.